Current perceptions and practices in lipid management: results of a European Society of Cardiology/European Atherosclerosis Society Survey. (18th January 2021) - Koskinas, Konstantinos C; Catapano, Alberico L; Baigent, Colin; Tokgozoglu, Lale; Mach, Francois
Abstract: Aims: We sought to evaluate physicians' opinions and practices in lipid management. Methods and results: A web-based survey by the European Society of Cardiology (ESC) and European Atherosclerosis Society (EAS) was distributed to 70 696 individuals at two time points, before and after publication of the 2019 ESC/EAS dyslipidaemia guidelines. Respondents (1271 in the first and 1056 in the second part) were most commonly cardiologists in Europe. More than 90% of participants reported that they regularly measure lipid levels and discuss lipid-lowering treatment with patients. More than 87% found the use of LDL-C goals useful or potentially useful, although it was acknowledged that recommended goals are frequently not achieved. Regarding the LDL-C goal according to the 2019 guidelines (<1.4 mmol/L for very high-risk patients), more than 70% of respondents felt that it is based on solid scientific evidence, but 31% noted that implementation should also consider available local resources and patient preferences. Statin intolerance was perceived as infrequent, affecting 1–5% of patients according to most respondents but was the main reason for not prescribing a statin to secondary-prevention patients, followed by patient non-adherence. Although most respondents reported that 11–20% of secondary-prevention patients have an indication to add a non-statin medication, fewer patients (<10% according to most respondents) receive these medications. Conclusions: This survey shows a high level of acceptance of the LDL-C treatment goals recommended by current ESC/EAS guidelines. Although patient-related factors were the main reported reasons for suboptimal lipid-lowering therapy, physician inertia to intensify treatment cannot be excluded as an additional contributing factor.